PENGARUH LITERASI KEUANGAN SYARIAH PENDAPATAN PERSEPSI RISIKO DAN PERILAKU KEUANGAN TERHADAP KEPUTUSAN INVESTASI EMAS ANTAM LOGAM MULIA PADA GENERASI MILENIAL - Jannah , Nisa Zahratul; Mahyarni, Mahyarni; Julina, Julina (Komunitas Manajemen Kompetitif, 2025)
This study was motivated by the increasing interest of the millennial generation in gold investment, but the low level of Islamic financial literacy and the absence of in-depth empirical studies in Pekanbaru City. The purpose of this study was to analyze the influence of Islamic financial literacy, income, risk perception, and financial behavior on investment decisions for Antam precious metal gold in the millennial generation. This study uses the Theory of Planned Behavior, Decision Theory, and Prospect Theory as theoretical foundations. The method used is a quantitative approach with a survey technique by distributing questionnaires to 100 millennial generation respondents in Pekanbaru City. Data analysis was carried out using validity, reliability tests, classical assumption tests, and multiple linear regression with the help of SPSS version 30. The results of the study showed that partially, income and financial behavior had a positive and significant effect on gold investment decisions, while Islamic financial literacy and risk perception did not have a significant effect. Simultaneously, the four independent variables had a significant effect on investment decisions. These findings indicate that healthy financial behavior and sufficient income levels are dominant factors in driving gold investment decisions. This study provides recommendations for financial institutions and providers of sharia gold products to be more active in educating sharia financial literacy, as well as developing marketing strategies that are adaptive to the preferences of the millennial generation. For academics, this study is expected to be a reference in developing studies on sharia investment and the financial behavior of the younger generation.